State- and individual-level predictors of Mexican death penalty support - Updegrove, Alexander H. (Crime & delinquency, 2018)
Mexico exerts a unique influence on Texas through immigration. As immigrants bring perspectives from their country of origin when they immigrate, studying attitudes toward capital punishment in Mexico may provide insight into ways Mexican immigrants could affect its future practice in Texas. Multilevel modeling is used to examine individual- and state-level predictors of death penalty support among a nationally representative sample of Mexicans. Results indicate age and Catholic affiliation are associated with death penalty support, although not in the expected directions, whereas states bordering the United States are less likely to support capital punishment, despite experiencing less overall peace and a higher average homicide rate. Findings suggest the need for researchers to use culture-specific factors to predict death penalty support.